Complements or substitutes? The contingent role of corporate reputation on the interplay between internal R&D and external knowledge sourcing. Issue 1 (February 2021) - Delgado-Verde, Miriam; Martín-de Castro, Gregorio; Cruz-González, Jorge; Navas-López, José Emilio
Abstract: Existing research does not provide a clear answer to the question of whether internal knowledge development and external knowledge sourcing are complementary or substitutive innovation activities. This paper adopts a contingent approach for addressing this issue by examining whether and how the interactive effect of internal R&D efforts and external knowledge sourcing on product innovation performance may be affected by the firm's corporate reputation. In doing so, a three-way interaction model is applied to a sample of 251 Spanish high-technology manufacturing firms. Interestingly, initial results support the substitutive argument: the positive effect of internal R&D on product innovation performance diminishes as the exposure to external knowledge increases. However, in well reputed companies, interaction becomes positive, revealing a complementary effect. Thus, the study extends the traditional approach focused on determining whether internal and external knowledge sourcing are complements or substitutes by showing that their interplay depends on other firm-specific characteristics. Moreover, identifying corporate reputation as a source of complementarity between both activities provides an additional explanation of how corporate reputation contributes to a more effective management of knowledge assets.